Persepsi Pemustaka terhadap Perpustakaan SMAN 2 Harau dalam Memenuhi Kebutuhan Informasi - Rella, Vinda Fasa; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractÂ The writing of this paper aims to describe the perceptions of visitors to the Library of SMAN 2 Harau in meeting information needs. The method used in this paper is a descriptive method with a quantitative approach. Then, the data was taken through distributing questionnaires to students of SMAN 2 Harau and interviews with librarians of SMAN 2 Harau.Â Based on the discussion it can be concluded. First, the perception of the user towards the service in the Library of SMAN 2 Harau has not been said to be good, because the Library of SMAN 2 Harau has not been able to support the fulfillment of information needed by the user, there are still many services that are very much needed and must be in the library, namely the absence of user guidance services for participants new students, lack of promotion from the library, then there is no internet service, and there are still many services that do not yet exist in this library that support other services such as photocopy services and storytelling services. Secondly, the user's perception of the existing collections in the SMAN 2 Harau Library cannot be said to be good, because the collection of periodicals has not been maximally procured, there are still many requests for information from users such as enrichment collections, and then the latest collections are not yet available. Third, the user's perception of the existing facilities at the SMAN 2 Harau Library was also said to be not good because this library had a room with facilities that were still lacking, such as inadequate bookshelves, lack of internet services, lack of custodians, and supporting facilities for the creation of conducive conditions such as air conditioners and TVs. Fourth, the perception of the librarian towards the attitude of the librarian in the SMAN 2 Harau Library is already good, because the librarian has provided hours of service in a timely manner, understands user needs, is quick in following up on librarian complaints, polite in providing services and proficient in finding books.Keywords: perception, users, information needs.Â